Hubungan Pengetahuan Remaja Putri Tentang Ca Mammae Dengan Perilaku Pemeriksaan Payudara Sendiri (Sadari) Di Sma Negeri 5 Kota Bengkulu - Inggani, Excelia Dwi; Hilinti, Yatri; Sari, Liya Lugita (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The World Health Organization (WHO) states that cancer is one of the leading causes of death from non-communicable diseases. In 2023, cancer caused approximately 9.7 million deaths, or 18.7% of all deaths worldwide per year. Breast cancer is the most common type of cancer in Indonesia, with nearly 70% of patients diagnosed at an advanced stage (Indonesian Health Profile, 2023). Data from Bengkulu Province indicates that 8,768 (2%) individuals underwent breast cancer screening using the SADARI method (Bengkulu Province Health Profile, 2023). The objective of this study was to determine the relationship between adolescent girls' knowledge about breast cancer and their self-breast examination (SADARI) behaviour at State Senior High School 5 in Bengkulu City. The method used was an analytical research design with a cross-sectional approach, and data were collected by distributing questionnaires to 84 respondents using simple random sampling. The results of the univariate analysis showed that nearly half of the respondents had insufficient knowledge (47.6%) and the majority of respondents did not perform SADARI (66.7%). The bivariate analysis revealed a significant relationship between adolescent girls' knowledge about breast cancer and their self-breast examination (SADARI) behaviour at SMA Negeri 5 Kota Bengkulu, with a p-value of 0.001. It is hoped that the school will collaborate with health workers to provide education about SADARI for the early detection of breast cancer.